IMPLEMENTASI METODE FUZZY SUGENO DALAMMELAKUKAN PENILAIAN TERHADAP HASIL KERAJINAN IBU PKK - Juanda Syahputra; Khairul Saleh (Smart Education, 2026)
The Family Empowerment and Welfare Group (PKK) is an important forum for community empowerment, especially for women, at the village and sub-district levels. One of the main activities carried out by PKK women is training and producing handicrafts aimed at improving creativity, skills, and the family's economic potential. In practice, the handicrafts made by PKK members are often assessed through competitions, exhibitions, or periodic evaluations. However, the assessment process is still often carried out manually and subjectively using handwritten assessment forms which are then added up to see the final result. The purpose of this study is to apply the fuzzy sugeno method to the assessment system for handicrafts from PKK women in Bandar Sono Village. The data used are product quality, creativity and innovation, economic value, and aesthetic value. Analysis of the Fuzzy Sugeno method shows that this approach is effective in converting qualitative data into quantitative values ??that can be interpreted clearly. Through the processes of fuzzification, inference, and defuzzification, this method is able to produce a final score that accurately reflects the quality level of the handicrafts. The test results for one data set show that a product with a Product Quality of 43, Creativity of 55, and Aesthetic Value of 60 has a recommendation level of